THE ANALYSIS OF E-COMMERCE RETARGETING STRATEGY TOWARD STUDENT PURCHASE INTENTION - Pinasang, Ian G.; Tulung, Joy E.; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
The advertising industry has experienced a major change during the past few years. Advertising on e-commerce can trace customer behavior in order to make the advertisement relevant with the customer past behavior on internet. The purpose of this study is to find out more about the perception of customer in retargeting advertisement to increase customer purchase intention This study employs multi linear regression to investigate the influence of consumer behavior. This study conducts with 100 Facebook user and e-commerce customer in Feb Unsrat as the respondents. Findings of this research show that discount, reference to previous visit, and advertisement frequency simultaneously influence customer purchase intention when they see retargeting advertisement in Facebook. Recommendation to this research advertising should be more minimalist, relevant, shorter, low frequency and for the advertisement companies should make some precautions, in order to minimise consumer suspicions for their data thus it might increase consumer purchase intentions.Â Keyword: retargeting, facebook, discount, reference to previous visit, advertisement frequency, e-commerce